Biometria de frutos e sementes, germinação e armazenamento de sementes de flor-de-seda [Calotropis procera (Aiton) W.T. Aiton] - Oliveira-Bento, Silvia Regina Silva de (2012)
The experiments were carried out in laboratory and greenhouse in the Universidade Federal Rural do Semiárido-UFERSA, to obtain information about the biometrics of fruits and seeds, germination and storage performance of silk flower seeds. In the first experiment there were evaluated length, width, thickness and weight of fruits and seeds in a 100 fruits size sample; the number of seeds per fruit was also quantified, moisture content and weight of 1000 seeds were obtained. Following traits were evaluated: germination and the germination average time. Experimental design was completely randomized with a 6x3x2 factorial, using combinations of six temperatures (20, 25, 30, 35, 20-30 e 25-30 ºC), three substrates (sand, towel paper and blotting paper) and two light conditions (presence and absence), with six replications of 50 seeds. In the second experiment seeds were used having moisture contents 30, 24, 18, 12 e 7%, packed in paper bags, plastic bags and plastic bottles, stored in cold chamber (16 °C a 18 °C) and laboratory (27 °C a 30 °C), both with 50-55%UR during 180 days.There were carried out periodic evaluations of moisture content, germination, seedling emergence, speed of emergence, seedling length and weight of seedling dry matter. The experimental design was completely randomized with a 6x5x3x2 factorial, using combinations of six storage periods, five moisture contents, three package types and two environmental conditions with four replications of 50 seeds. Data were analyzed by analysis of variance using test F. To comparisons between storage periods there were adjusted regression equations. The average weight of fruits was 23,53 g with average dimensions of 11,60 cm lenght, 7,41 cm width and 6,79 cm thickness; 54,6% of fruits showed from 401 to 500 seeds. The average dimensions of seeds were 0.75 cm length, 0,55 cm width and 0,10 cm thickness, while thousand seed weight was 8.54 g. It was concluded that there is variability for traits related to fruit size and weight of silk-flower, the number of seeds per fruit is high, favoring the specie spreading, widely distributed in the semiarid region; it is recommended that the initial and final counting of germination test are performed at 5 and 10 days after sowing, respectively; the constant temperature of 30 ° C, alternating 25-30 ° C and the substrates sand and towel paper were the most appropriate conditions for germination; silk flower seeds are indifferent to light, having orthodox physiological behaviour; seeds viability decreased with storage time of 180 days; seeds can be preserved with efficiency in paper bags, in a controlled environment, with moisture content of 7% for 90 days